The tumour suppressor ASPP2 plays a novel role in the maintenance of epithelial cell polarity - Sottocornola, R (2010)
ASPP2 has been identified as a haploinsufficient tumour suppressor in mice, and an activator of the apoptotic function of the p53 family. Yeast two-hybrid experiments have also shown that ASPP2 interacts with a large number of proteins involved in other major signalling pathways. The mechanism(s) of action of ASPP2 are therefore complex, and likely to involve more than just the stimulation of the apoptotic programme. Since a study previously conducted in our laboratory revealed that the deletion of ASPP2 in vivo leads to severe hydrocephalus in the J129/C57BL6 background (Vives et al., 2006), it can be hypothesised that ASPP2 safeguards the normal development of the mammalian central nervous system (CNS), in addition to its role as a tumour suppressor. Deletion of ASPP2 leads to the development of hydrocephalus, most probably by affecting tight junctions (TJs) in the choroid plexus, thereby impairing its bloodcerebrospinal fluid (CSF) barrier function. TJ defects are likely to be the underlying cause of the loss of cell polarity observed in the neuroepithelium of several areas of the CNS. As cell polarity plays a key role in multiple aspects of CNS development, ASPP2 appears to be required for the proper lamination of the cerebral cortex and retina. In addition to a loss of polarity, ASPP2 mutant neural stem cells (NSCs) exhibit increased proliferation accompanied by a shortening of the cell cycle, and form neuroblastic rosettes which resemble primitive neuroectodermal tumours. Lack of differentiation in the neo and postnatal cerebral cortex is also a feature of ASPP2 mutant mice. The ability of ASPP2 to inhibit the transcription of Notch target genes provides a novel mechanism by which ASPP2 may inhibit cell growth and promote differentiation. Since several tumour suppressors have been identified to be major players in cell polarity, and a loss of polarisation is a hallmark of cancer, the ability of ASPP2 to maintain cell polarity may further contribute towards its tumour suppressive function.